URGENSI PERATURAN PEMERINTAH TENTANG PERDAGANGAN ELEKTRONIK DALAM KAITANNYA DENGAN PENERAPAN PAJAK PADA TRANSAKSI E-COMMERCE - Nanin Koeswidi Astuti (to-ra, 2015)
Abstract E-commerce is a trade in goods and services via the Internet or other electronic means. Legally e-commerce transactions without knowing the geographic boundaries will cause a lot of problems in practice in the field on the issue of taxation of income from e-commerce transactions conducted. Whether existing tax provisions currently supports e-commerce transactions and whether the urgency of government regulations on electronic commerce to taxation on e-commerce transactions. This study is a literature review with descriptive design. The results showed that the existing tax provisions not support e-commerce transactions themselves. Regarding the determination of an e-commerce transaction is considered to have a permanent establishment (BUT) in relation to the subject of taxes, UU RI No. 36 year 2008 Article 5, paragraph (1) letter p on permanent establishment, but this provision is not complete because it has not explained in specific about the types of e-commerce transactions as recommended in the OECD TAG that there are 28 types of transactions that most of the e-commerce transactions generate revenues and royalties. Seeing the enormous potential state revenues from the sector income tax taxpayers in e-commerce transactions that, then the urgency of government regulations on electronic commerce to taxation on e-commerce transactions should be enacted so happens legal certainty in e-commerce transactions and government as authorities levy taxes. But before electronic trading RPP passed into government regulation, should DJP need more in-depth assessment of the contents of RPP with related parties transactions involving e-commerce. Kata Kunci: Penerapan Pajak Elektronik dan Transaksi E-Commerce